2016
DOI: 10.1111/cob.12136
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and weight loss outcomes for patients with complex obesity, anxiety and depression attending a weight management programme with targeted psychological treatment

Abstract: Attrition and weight loss outcomes for patients with complex obesity, anxiety and depression attending a weight management programme with targeted psychological treatment. Clinical Obesity, 6(2), pp. 133-142. (doi:10.1111/cob.12136) This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/118709/ What is already known about this subject?• Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 36 publications
5
38
2
1
Order By: Relevance
“…Two studies reported BMI in stratified groupings which left the accumulative average BMI calculated from 16 studies at 42.54 kg/m 2 . Baseline weight in kilograms was also reported by 90% of included studies except for Morrison et al (2011) and Turner et al (2015) . Turner et al reported participants that lost weight at 12 months, which was their intervention endpoint .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Two studies reported BMI in stratified groupings which left the accumulative average BMI calculated from 16 studies at 42.54 kg/m 2 . Baseline weight in kilograms was also reported by 90% of included studies except for Morrison et al (2011) and Turner et al (2015) . Turner et al reported participants that lost weight at 12 months, which was their intervention endpoint .…”
Section: Resultsmentioning
confidence: 95%
“…Baseline BMI was reported by 90% of included studies except for Turner et al (2015) and Wright et al (2012) and ranged from 30.1 to 49.1 kg/m 2 . Two studies reported BMI in stratified groupings which left the accumulative average BMI calculated from 16 studies at 42.54 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations